The Influence of ROA, DER, and TATO on the Stock Prices of Investment Services Trading Companies on the IDX - Febrianti, Reni; Mujanah, Siti; Halik, Abdul (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
In the modern era, business development is increasing, and many companies are going public. Every company certainly strives to maintain and develop its business in order to compete and gain profits. One way to do this is by registering company shares on the capital market and then selling shares to investors. This study aims to determine the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and Total Assets Turnover (TATO) on stock prices in companies in the trading, services, and investment sectors listed on the Indonesia Stock Exchange in 2018-2021. The research method used is quantitative, with purposive sampling. From the results of the study, the ROA variable partially does not affect stock prices. The results of the partial test (t) of the ROA variable (X1) show a significance value of 0.972> 0.05 and a calculated t value of 0.035 < ttable 1.67252. The DER variable partially affects stock prices. The partial test result (t) of the DER variable (X2) shows a significance value of 0.000 <0.05 and a calculated t value of -5.520> t table -1.67252. The TATO variable partially influences stock prices. The calculated result of the TATO variable (X3) shows a significance value of 0.012 <0.05 and a calculated t value of 2.612> t table 1.67252. The ROA, DER, and TATO variables simultaneously influence stock prices. The results of the Simultaneous Test (F) show a significance value of 0.000 <0.05 and a calculated f value of 15.843> 2.78 f table..